Endonasal endoscopic surgical treatment of craniopharyngiomas in adult patients. Our experience - Mykola O. Guk; Andriy A. Chukov (Ukrainian Neurosurgical Journal, 2023)
Objective: to estimate the results of surgical treatment of adult patients with craniopharyngiomas (CP), who underwent endoscopic endonasal surgical treatment. Materials and methods. Treatment of 69 adult patients with CPs who underwent endonasal endoscopic surgery from 2014 to 2021 is described. Gender division: women 42% (60.9%), men 27 (39.1%). The minimum age of patients is 19 years (women 19, men 20), the maximum age is 73 years (women 73, men 66). The mean age of all patients in the group was 46.7±14.5 years, women 47.6±15.5 years, men 45.1±12.6 years. In 52 patients (75.4%) the surgical intervention was primary, and in 17 patients (24.6%) it was secondary. All patients were estimated for preoperative and postoperative endocrine and neuro-ophthalmological status in dynamics. Results. No hemorrhagic or access-associated complications have been reported. Major complications: postoperative CSF leak - 9 patients (13%), meningitis - 10 patients (14.5%), 7 out of 8 patients with CSF leak had meningitis. 7 out of 10 patients with meningitis also had CSF leak. Other complications: acute tension pneumocephalus (2 cases, 2.9%), electrolyte disturbances (45 cases, 65.2%), severe diencephalic dysfunction (SDD) (4 cases, 5.8%). The postoperative mortality rate was 3 cases (4.35%), of which 1 due to meningitis (33.3% of all deaths), due to SDD 2 cases (66.6%). The dynamic changes of visual function were as follows: improvement in 36 patients (66.7% of all patients with preoperative visual impairment), no significant change in 7 patients (13%), deterioration in 10 patients (18.5%), 4 of which were transient. 40 patients had hypopituitarism prior to surgery, 10 of whom also had diabetes insipidus. A worsening of hypopituitarism was observed in 13 patients (32.5% of all patients with preoperative hypopituitarism) and an onset of hypopituitarism in 18 patients (26.1%). The onset of diabetes insipidus in the postoperative period occurred in 23 patients (33.3%), 7 of whom with regression. Conclusions. Endonasal endoscopic approach is no longer an alternative for surgical treatment of certain forms of craniopharyngiomas, but it is a method of choice for most CP cases. The postoperative mortality is low. The quality of life of the operated patients is satisfactory due to a high percentage of improvement in visual function and preservation of endocrine function. The rates of CSF leak and purulent-septic complications correlate with the data of the world literature. Modern standards of treatment require the establishment of a multidisciplinary team of specialists in healthcare institutions to personalize the treatment process in patients with CPs.